2001
DOI: 10.1046/j.1464-410x.2001.00998.x
|View full text |Cite
|
Sign up to set email alerts
|

A dose‐escalation study to assess the efficacy and safety of sildenafil citrate in men with erectile dysfunction

Abstract: Objective To assess the ef®cacy and safety of sildena®l citrate (Viagra 1 , P®zer Inc., USA) in a double-blind, placebo-controlled, dose-escalation study over a period of 26 weeks in men with erectile dysfunction of a broad spectrum of aetiology. Patients and methods In all, 315 patients from ®ve countries were randomized to receive treatment with placebo (156 men) or sildena®l (159 men). Signi®cant concomitant medical conditions were hypertension (20%), a history of pelvic surgery (19%), diabetes mellitus (15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
20
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 22 publications
9
20
1
Order By: Relevance
“…15 -17 Slightly higher post-treatment scores were observed for both drug and placebo conditions in the two Asian studies, 18,19 suggesting that Asian men might be slightly more susceptible to the nonspecific effects of treatment. However, the drugplacebo differences on Q3, Q4, and the EF domain were highly similar to those observed in both the European 16,17 and US 15 studies. Strong correlations were noted with other measures of treatment outcome (event logs, global efficacy ratings) in all five studies.…”
Section: Comparison Of Studiessupporting
confidence: 80%
See 2 more Smart Citations
“…15 -17 Slightly higher post-treatment scores were observed for both drug and placebo conditions in the two Asian studies, 18,19 suggesting that Asian men might be slightly more susceptible to the nonspecific effects of treatment. However, the drugplacebo differences on Q3, Q4, and the EF domain were highly similar to those observed in both the European 16,17 and US 15 studies. Strong correlations were noted with other measures of treatment outcome (event logs, global efficacy ratings) in all five studies.…”
Section: Comparison Of Studiessupporting
confidence: 80%
“…16,17 The first study 16 was conducted in six countries (Denmark, Ireland, Italy, Norway, Sweden, UK). In this study, 514 patients with ED of mixed etiologies were randomly assigned to 12 weeks of treatment with placebo or with a fixed dose of 25, 50 or 100 mg of sildenafil.…”
Section: European Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the mean change in score in the EF domain among responders (sensitivity) was 12.8 for the English IIEF, 6 while it was only 6.0 for the Malay IIEF. Interestingly, the mean change in EF domain scores observed in trials of sildenafil 3,11 conducted in Asia was about 11, which was similar to those observed in US 12 and European 13 trials. On that basis, a recent review of IIEF 4 suggests that the IIEF (or at least its EF domain) was a robust measure in different countries and cultures.…”
Section: Validation Of the Malay Iiefsupporting
confidence: 76%
“…Of them, a total of 13 trials fulfilled all inclusion criteria and were included in the meta-regression analysis. [23][24][25][26][27][28][29][30][31][32][33][34][35] Characteristics of the included trials are presented in Table 1.…”
Section: Included Trialsmentioning
confidence: 99%